External drivers of institutional change in Central Asia: Regional integration schemes and the role of Russia and China - Rainer Schweickert; Inna Melnykovska; Hedwig Plamper (Kiel Institute for the World Economy (IfW), 2012)
Russia and China are assumed to challenge democratization and to promote autocracy. In a first step, we analyze Central Asia as the most-likely case, considering both Russia and China as relevant external actors. We develop a concept for our analysis based on the different strategies of Russia (dominance) and China (doing-business) towards the region and present the results of a qualitative study of the main dimensions of autocracy promotion with respect to regional and bilateral schemes. In a second step, we extend a previous framework (Melnykovska and Schweickert 2011) and provide econometric evidence based on a panel of post-socialist countries. We show that bilateral schems are (still) more relevant for external influences in Central Asia and that (unintentionally) China's doing-business approach may in fact promote institutional change. Arguably, democratization should not be a precondition for cooperation as in European Neighbourhood Policy (ENP) but rather be promoted by sweeping economic cooperation incentives.
Keywords: F53; F59; 330; Central Asia; China; Russia; governance; regional integration; trade; minorities; military threat; Autoritäres System; Russland; China; Handelsregionalismus; Internationale Wirtschaftsbeziehungen; Governance-Ansatz; Demokratisierung; Zentralasien